Genetic dysregulation of endothelin-1 is implicated in coronary microvascular dysfunction - Ford, Thomas J; Corcoran, David; Padmanabhan, Sandosh; Aman, Alisha; Rocchiccioli, Paul; Good, Richard; McEntegart, Margaret; Maguire, Janet J; Watkins, Stuart; Eteiba, Hany; Shaukat, Aadil; Lindsay, Mitchell; et al. (European heart journal, 2020)
Endothelin-1 (ET-1) is a potent vasoconstrictor peptide linked to vascular diseases through a common intronic gene enhancer [(rs9349379-G allele), chromosome 6 (PHACTR1/EDN1)]. We performed a multimodality investigation into the role of ET-1 and this gene variant in the pathogenesis of coronary microvascular dysfunction (CMD) in patients with symptoms and/or signs of ischaemia but no obstructive coronary artery disease (CAD). Three hundred and ninety-one patients with angina were enrolled. Of these, 206 (53%) with obstructive CAD were excluded leaving 185 (47%) eligible. One hundred and nine (72%) of 151 subjects who underwent invasive testing had objective evidence of CMD (COVADIS criteria). rs9349379-G allele frequency was greater than in contemporary reference genome bank control subjects [allele frequency 46% (129/280 alleles) vs. 39% (5551/14380); P = 0.013]. The G allele was associated with higher plasma serum ET-1 [least squares mean 1.59 pg/mL vs. 1.28 pg/mL; 95% confidence interval (CI) 0.10-0.53; P = 0.005]. Patients with rs9349379-G allele had over double the odds of CMD [odds ratio (OR) 2.33, 95% CI 1.10-4.96; P = 0.027]. Multimodality non-invasive testing confirmed the G allele was associated with linked impairments in myocardial perfusion on stress cardiac magnetic resonance imaging at 1.5 T (N = 107; GG 56%, AG 43%, AA 31%, P = 0.042) and exercise testing (N = 87; -3.0 units in Duke Exercise Treadmill Score; -5.8 to -0.1; P = 0.045). Endothelin-1 related vascular mechanisms were assessed ex vivo using wire myography with endothelin A receptor (ETA) antagonists including zibotentan. Subjects with rs9349379-G allele had preserved peripheral small vessel reactivity to ET-1 with high affinity of ETA antagonists. Zibotentan reversed ET-1-induced vasoconstriction independently of G allele status. We identify a novel genetic risk locus for CMD. These findings implicate ET-1 dysregulation and support the possibility of precision medicine using genetics to target oral ETA antagonist therapy in patients with microvascular angina. ClinicalTrials.gov: NCT03193294.